CO2 on a tightrope: stabilization, room-temperature decarboxylation, and sodium-induced carboxylate migration - Häußermann, Achim; Rominger, Frank; Straub, Bernd Franz (2012)
A sterically shielded 3-substituted zwitterionic N,N-dimethylisotryptammonium carboxylate has been synthesized by consecutive chemoselective double alkylation of indole. The carboxylate undergoes a quantitative and unusually facile decarboxylation in dimethyl sulfoxide (DMSO) or dimethyl formamide (DMF) at room temperature. The breaking of a nearly equidistant hydrogen bond by solvent molecules initiates heterolytic CC cleavage. The decarboxylation rate decreases with increasing CO2 partial pressure, proving the competitiveness of protonation and re-carboxylation of the carbanionic intermediate. Corresponding spiro compounds containing silylene and stannylene moieties show high thermal stability. Addition of an excess of methyllithium to the sodium salt triggers a reaction sequence comprising a deprotonation, carboxylate transfer, and nucleophilic trapping of the rearranged carboxylate by another equivalent of methyllithium. Hydrolytic work-up of the geminal diolate leads to an acetyl product. The role of the sodium counterion and the mechanism of the rearrangement have been unraveled by deuteration experiments.